Thermoresponsive Nanocomposite Hydrogels: Transparency, Rapid Deswelling and Cell Release - Hou, Yaping (2011)
Thermal modulation reversibly switches poly(N-isopropylacrylamide) (PNIPAAm) hydrogels between a water-swollen and a deswollen state which is useful for a variety of biomedical applications. The utility and efficiency of PNIPAAm hydrogels requires tailoring their rate of deswelling/reswelling, mechanical properties and/or optical clarity. In the current work, we prepared novel thermoresponsive nanocomposite hydrogels comprised of a PNIPAAm hydrogel matrix and polysiloxane colloidal nanoparticles (~54 nm ave. diameter) via in situ photopolymerization of aqueous solutions of NIPAAm monomer, N,N′-methylenebisacrylamide (BIS, crosslinker), photoinitiator and 0.5–4.0 wt% polysiloxane nanoparticles (wt% solids of nanoparticles with respect to NIPAAm weight) at ~7 °C. At these nanoparticle concentrations, the nanocomposite hydrogels were more optically transparent versus those prepared with analogous larger nanoparticles (~219 nm ave. diameter). The volume phase transition temperature (VPTT) of the nanocomposite hydrogels was conveniently unaltered versus that of the pure PNIPAAm hydrogel. Incorporation of nanoparticles caused enhancement in modulus as well as the extent and rate of deswelling. When cooled from 37 °C to 25 °C, mouse smooth muscle precursor cells (10T1/2) were effectively detached from nanocomposite hydrogel surfaces due to hydrogel swelling.